Pengaruh Penggunaan Model Pembelajaran PBL dan Gaya Belajar terhadap Hasil Belajar Siswa Mata Pelajaran IPAS: The Influence of the Use of the PBL Learning Model and Learning Styles on Student Learning Outcomes in the Science Subject - Juniam Roselina; Dwi Fauzia Putra; Tri Wahyudianto; Suwito Suwito (ITScience (Information Technology and Science), 2026)
The low learning outcomes of students in Natural and Social Sciences (IPAS) subjects in elementary schools are influenced by the use of conventional learning methods that fail to accommodate the diversity of students' learning styles. This condition causes students to be less active and less motivated, and to have difficulty understanding the material in context. This study aims to determine the relationship between the implementation of Problem-Based Learning (PBL) and learning styles on the learning outcomes of fifth-grade students of SDN Mranggon Lawang I. This study uses a quantitative approach with an ex post facto correlational research type. The research sample consisted of 32 fifth-grade students selected through purposive sampling. Data were collected through questionnaires, observations, interviews, and documentation. Data analysis was conducted using simple and multiple linear regression in SPSS version 27. The results showed that implementing PBL is positively associated with students' IPAS learning outcomes. Learning styles were also significantly related to learning outcomes. Simultaneously, the implementation of PBL and learning styles is related to improvements in students' IPAS learning outcomes. These findings indicate that Problem-Based Learning, adapted to students' learning characteristics, can foster a more active and meaningful learning process. The implementation of Problem-Based Learning (PBL) and students' learning styles are positively associated with science learning outcomes in this study. However, the results cannot be widely generalized due to the limited sample size and the study's location, which was limited to one elementary school. Therefore, further research with a more diverse sample and a more robust research design is needed to obtain more comprehensive results.